2016
DOI: 10.3126/ojn.v6i2.17412
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of different Skeletal pattern in Patients seeking Orthodontic Treatment in Mid-western Nepal

Abstract: Objective: To determine the distribution of different skeletal pattern in orthodontic patients visiting a tertiary center in midwestern Nepal.Materials & Method: A sample of 200 lateral cephalograms of Nepali patients visiting UCMS-College of Dental Surgery, Bhairahawa was obtained. The jaw base relationship was assessed from lateral cephalograms using angular measurement (ANB angle). Among the total sample size; 74 (37%) were males and 126 (63%) were female. Age was divided into 3 groups: 8-11 years, 12-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This sequence was consistent with the findings of Halwai et al conducted in mid-western Nepal. 6 Piya et al found highest number of orthodontic patients in adolescent age group. 4 The difference could be due to higher consciousness for esthetics and sound economic condition of the patients in adult age group among the present sample.…”
Section: -11mentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence was consistent with the findings of Halwai et al conducted in mid-western Nepal. 6 Piya et al found highest number of orthodontic patients in adolescent age group. 4 The difference could be due to higher consciousness for esthetics and sound economic condition of the patients in adult age group among the present sample.…”
Section: -11mentioning
confidence: 99%
“…Although many studies have been conducted regarding the type and distribution of malocclusion in different regions of Nepal; [2][3][4][5][6][7] very few researches of such kind have been conducted in south-eastern Nepal. The objective of the study was to assess the pattern of distribution of malocclusion among orthodontic patients in south-eastern region of Nepal, to determine the association between dental and skeletal malocclusion, and to estimate the age of presentation of Class II malocclusion among the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou reported Class I jaw relationship as the most common relationships among the Chinese population followed by Class III and Class II 26 . Halwai showed the most common skeletal jaw relationship was skeletal Class II followed by Cl I and Cl III in Midwestern Nepal 13 .…”
Section: Discussionmentioning
confidence: 97%
“…Dento-skeletal abnormalities can adversely impact the psychological, emotional, and overall well-being and quality of life in children 13 . Therefore, planning the orthodontic treatment requires understanding the patient's baseline demographics and the prevalence of different skeleto-dental abnormalities among the population.…”
Section: Discussionmentioning
confidence: 99%
“…More patients in this region reported for orthodontic treatment during adolescence which is comparable to results obtained by Piya et al 9 However, Halwai et al reported higher number of adult orthodontic patients. 10 This could be because patients and their guardians are more concerned and are aware about necessity of the orthodontic treatment at this age.…”
Section: Discussionmentioning
confidence: 99%